Episoden, Figuren: The Concept of Musical and Instrumental Theater in the Contemporary Music Interpretation - Pescada, Gonçalo André Dias (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The combination of scenic action and music, known as "musical theatre," corresponds to a technique used by composers such as Satie and Debussy in the History of Music. As a result, the concept of "instrumental theatre" emerges as a concept in which musicians play the roles of actors. Mauricio Kagel considers himself to be one of the composers who has most explored the aspects of staging related to musical performance, attributing to the interpreter also actor functions such as: adopting certain facial expressions while playing, entering the stage in a specific way, interacting physically with other artists, and so on. The research method used in this article it was based on analysis and performance of the work Episoden Figuren, through the audition, experience and observation with others interpreters and musicians, colleting relevant literature to understand the composer points of view and to understand a period where many characteristics of our daily life emerge as an integrant part of composition process: speaking, lauhging, smiling, among others. In this process, the interpreter becomes an actor, performer, an artist.